2021
DOI: 10.1088/1757-899x/1011/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Baeckea frutescen L. essential oil was tested with Aedes aegypti larvae at various concentration levels

Abstract: Reducing the negative impact of using synthetic insecticides in a friendly manner. The alternative is to use a bioinsecticide. Ujung Atap (Baeckea frutescens L.) essential oil is one of them that has the potential as a bioinsecticide. Distillation of fresh leaves and dry leaves. Aedes aegypti larvicide mortality test on the resulting essential oil. A. aegypti mosquitoes that cause dengue fever. Analyze the essential oil content of B. frutescens L. by GC-MS. The Dried Leaf Distillation of B. Frutescens L. produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Local Bangka Belitung plants such as the broom plant (Baeckea frutescen L) from the Myrtaceae family have potential as insecticides [11]. The combination of citronella waste (Cymbopogon nardus L) which still contains geraniol and citronella with broom and rice plants has the potential to produce formulations that can be used as insecticides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local Bangka Belitung plants such as the broom plant (Baeckea frutescen L) from the Myrtaceae family have potential as insecticides [11]. The combination of citronella waste (Cymbopogon nardus L) which still contains geraniol and citronella with broom and rice plants has the potential to produce formulations that can be used as insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, it was found that citronella oil from C. nardus L. has the potential as a biopesticide and insecticide [12,13]. Baeckea frutescen L contains essential oils of esters and produces essential oils of 0.071% and has potential as a fungicide and larvicide [8,11,14]. Therefore, testing the essential oil content of B. frutescen L and C. nardus L. from Bangka Belitung is necessary to obtain the right formulations in development to be used as natural insecticides.…”
Section: Introductionmentioning
confidence: 99%